Polish-English Terminology of Tari Law as a Challenge for an ESP Translator - Monika Dyńska (Language, Culture, Politics)
This study attempts to examine the following phenomena: translator's experience and linguistic competence (their hierarchy) in the process of translating specialistic texts in the field of tariff law as well as the equivalence of translations in the abovementioned subject matter. It was examined whether translators unfamiliar with the terminology of tariff law (without experience) make the right choice of equivalents used in both languages, and whether the increase in language competences of students of English philology with the specialization in applied translation affects the quality of translation of specialistic texts and compensates for the lack of the above-mentioned experience. As expected, the terminology of the tariff law is a challenge for the translator. Only thanks to the combination of excellent knowledge of the specialized language with excellent knowledge of the source and target language, it was possible to achieve a high degree of equivalence of specialistic texts in the field of tariff law. Finally, the increase in the language competence of students to some extent compensated for the lack of experience in tariff law.